Multimedia Annotations for Practical Collaborative Reasoning - Manuel Cebrián-; María Jesús Gallego-Arrufat; Violeta Cebrián-Robles (Springer, 2021)
University education requires students to be trained both at university and at external internship centres. Because of Covid-19, the availability of multimedia resources and examples of practical contexts has become vital. Multimedia annotation can help students reflect on the professional world, collaborating and interacting with colleagues online. This study aims to encourage collaborative practical thinking by using new video annotation technologies. 274 students participated in an experiment of task design focusing on the analysis of a technology-based, award-winning educational innovation project. With mixed research design, qualitative and quantitative data exported from the video annotation platform used was collected and analysed. The results show differences in the quality and quantity of the answers: in the tasks with broad Folksonomy they are more numerous but more dispersed in their analysis, and vice versa. The quality of the answers given with narrow Folksonomy is also higher in both texts and videos modes. Producing multimedia annotations is a practical way to encourage students to practise reflective reasoning about the professional reality.